Analysis of Financial Performance Before and After Ipo (Initial Public Offering) on Company Share Acceleration Boards on The Indonesia Stock Exchange - Handi Jovian; Nizwan Zukhri; Ari Agung Nugroho (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study aims to determine whether there is a difference between the liquidity ratio proxied by current assets, the solvency ratio proxied by the debt to equity ratio, and the profitability ratio proxied by return on assets and return on equity on shares of acceleration board companies that carry out initial public offerings. (IPO) on the Indonesian stock exchange in 2020. This study uses a quantitative approach. The data collection technique uses a literature study, namely by studying literature, notes, research journals, scientific works, and books related to theories and problems to be discussed and then added with the documentation method. The source used is secondary data in the form of financial report data of the acceleration board company that will be studied. The sampling technique was using purposive sampling method with a total of 5 companies. The analytical method used is descriptive analysis and paired sample t-test analysis. The results of the study stated that there were no significant differences in all variables, namely current assets, debt to equity ratio, return on assets and return on equity at the time before carrying out the IPO (Initial Public Offering) and after the IPO (Initial Public Offering) on ​​stocks. acceleration board companies on the Indonesian stock exchange in 2020. Keywords: Initial Public Offering, Acceleration Board Shares, Current Assets, Debt to Equity Ratio, Return on Assets, and Return on Equity